An Exploration of the Serotonin System in Antisocial Boys with High Levels of Callous-Unemotional Traits - Moul, Caroline (Public Library of Science, 2013)
BACKGROUND: The serotonin system is thought to play a role in the aetiology of antisocial and aggressive behaviour in both adults and children however previous findings have been inconsistent. Recently, research has suggested that the function of the serotonin system may be specifically altered in a sub-set of antisocial populations – those with psychopathic (callous-unemotional) personality traits. We explored the relationships between callous-unemotional traits and functional polymorphisms of selected serotonin-system genes, and tested the association between callous-unemotional traits and serum serotonin levels independently of antisocial and aggressive behaviour. METHOD: Participants were boys with antisocial behaviour problems aged 3–16 years referred to University of New South Wales Child Behaviour Research Clinics. Participants volunteered either a blood or saliva sample from which levels of serum serotonin (N = 66) and/or serotonin-system single nucleotide polymorphisms (N = 157) were assayed. RESULTS: Functional single nucleotide polymorphisms from the serotonin 1b receptor gene (HTR1B) and 2a receptor gene (HTR2A) were found to be associated with callous-unemotional traits. Serum serotonin level was a significant predictor of callous-unemotional traits; levels were significantly lower in boys with high callous-unemotional traits than in boys with low callous-unemotional traits. CONCLUSION: Results provide support to the emerging literature that argues for a genetically-driven system-wide alteration in serotonin function in the aetiology of callous-unemotional traits. The findings should be interpreted as preliminary and future research that aims to replicate and further investigate these results is required.